Current trends in pricing for state defense order products - S. A. Polukhina (Путеводитель предпринимателя)
The issues of pricing for products of the state defense order are considered. The classification of methods of procurement of weapons, military and special equipment is given. The main types of contract prices and methods of forming the initial maximum contract price are determined. Particular attention is paid to approaches to pricing for products of the state defense order for the case of a single supplier (contractor, execute). The modern norms of the law are presented, which allow optimizing budget funds by choosing an option that ensures the achievement of technical results and minimizing costs throughout the life cycle of weapons, military and special equipment.